The KdmB-EcoA-RpdA-SntB (KERS) chromatin regulatory complex controls development, secondary metabolism and pathogenicity in Aspergillus flavus - Karahoda, Betim; Pfannenstiel, Brandon T.; Sarikaya-Bayram, Özlem; Dong, Zhiqiang; Ho Wong, Koon; Fleming, Alastair B.; Keller, Nancy P.; Bayram, Özgür (Fungal genetics and biology, 2023)
•KdmB-EcoA-RpdA-SntB complex was identified and characterized in A. flavus.•ecoA deletion is lethal whereas rpdA deletion is not lethal in A. flavus.•Similar to sntB, both kdmB and rpdA are essential for aflatoxin B1 production.•KERS is required for sclerotia formation, sporulation and expression of secondary metabolite gene clusters.•kdmB and rpdA control histone modifications. The filamentous fungus Aspergillus flavus is a plant and human pathogen predominantly found in the soil as spores or sclerotia and is capable of producing various secondary metabolites (SM) such as the carcinogenic mycotoxin aflatoxin. Recently, we have discovered a novel nuclear chromatin binding complex (KERS) that contains the JARID1-type histone demethylase KdmB, a putative cohesion acetyl transferase EcoA, a class I type histone deacetylase RpdA and the PHD ring finger reader protein SntB in the model filamentous fungus Aspergillus nidulans. Here, we show the presence of the KERS complex in A. flavus by immunoprecipitation-coupled mass spectrometry and constructed kdmBΔ and rpdAΔ strains to study their roles in fungal development, SM production and histone post-translational modifications (HPTMs). We found that KdmB and RpdA couple the regulation of SM gene clusters with fungal light-responses and HPTMs. KdmB and RpdA have opposing roles in light-induced asexual conidiation, while both factors are positive regulators of sclerotia development through the nsdC and nsdD pathway. KdmB and RpdA are essential for the productions of aflatoxin (similar to findings for SntB) as well as cyclopiazonic acid, ditryptophenaline and leporin B through controlling the respective SM biosynthetic gene clusters. We further show that both KdmB and RpdA regulate H3K4me3 and H3K9me3 levels, while RpdA also acts on H3K14ac levels in nuclear extracts. Therefore, the chromatin modifiers KdmB and RpdA of the KERS complex are key regulators for fungal development and SM metabolism in A. flavus.